Rastlinski izvlečki ekstrakcije s superkritičnimi tekočinami in njihova uporaba - Kramberger, Katja (Farmacevtski vestnik, 2019)
Supercritical fluid extraction method is relatively new plant extraction method, which is more effective, selective and environment-friendlier alternative to conventional extraction procedures. In the article we present procedures for obtaining supercritical CO2 plant extracts and advantages of their use in the field of pharmacy, nutrition and cosmetics, illustrated by practical examples.
Keywords: bioaktivne spojine; Ekstrakcija (kemija); ekstrakcija s superkritičnim CO2; izolacija spojin; rastlinski izvlečki